2023
DOI: 10.3390/v15020286
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Host Range of Ackermannviridae Bacteriophages through Chimeric Tailspike Proteins

Abstract: Host range is a major determinant in the industrial utility of a bacteriophage. A model host range permits broad recognition across serovars of a target bacterium while avoiding cross-reactivity with commensal microbiota. Searching for a naturally occurring bacteriophage with ideal host ranges is challenging, time-consuming, and restrictive. To address this, SPTD1.NL, a previously published luciferase reporter bacteriophage for Salmonella, was used to investigate manipulation of host range through receptor-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 68 publications
1
16
0
1
Order By: Relevance
“…Indeed, in silico analysis of tsp genes in the Ackermannviridae family has suggested that tsp genes undergo homologous recombination due to the conserved N-termini of the four genes 12 . Our study showed that homologous recombination can exchange tsp genes and still produce infectious phages without disrupting the TSP complex, similar to a recent study 28 . While we showed exchange within the family, other in-silico analyses of TSPs in the Ackermannviridae family have demonstrated that the receptor binding domains are exchanged with distant related lytic phages and prophages 11,12,16 .…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, in silico analysis of tsp genes in the Ackermannviridae family has suggested that tsp genes undergo homologous recombination due to the conserved N-termini of the four genes 12 . Our study showed that homologous recombination can exchange tsp genes and still produce infectious phages without disrupting the TSP complex, similar to a recent study 28 . While we showed exchange within the family, other in-silico analyses of TSPs in the Ackermannviridae family have demonstrated that the receptor binding domains are exchanged with distant related lytic phages and prophages 11,12,16 .…”
Section: Discussionsupporting
confidence: 91%
“…Next to serogroup prediction, RBDs of Lederbergand Uetakeviruses with a podovirus morphotype have been successfully grafted into myo-like phage tail-like bacteriocins (PTLBs) (Scholl et al, 2009(Scholl et al, , 2012 to successfully swap the killing spectrum of the PTLB. In addition, many RBDs of RBPs of Kutterviruses share homology to those of Lederbergor Uetakeviruses, such as TSP3 of phage SPTD1 (Gil et al, 2023) and to other RBDs identi ed in this work. This shows that Lederbergand Uetakeviruses are ideal candidates as a start point to identify a RBP targeting an O-antigen serogroup of interest and expand from there to recruit more RBPs belonging to the same RBP subtype from phages belonging to other taxonomic groups.…”
Section: Discussionmentioning
confidence: 60%
“…Przondovirus K11, a phage related to Kayfunaviruses, has been successfully engineered by swapping the RBD to alter the host range towards different Klebsiella capsular serotypes (Latka et al, 2021). Similarly, Kuttervirus phage SPTD1 RBDs have been swapped within the same phage genus to target different Salmonella O-antigen serogroups (Gil et al, 2023). Additionally, the RBDs of podo-like Lederbergand…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of TSP2 revealed that SilasIsHot also contains a unique TSP2. Little is known about the TSP2-5 subtype of SilasIsHot, while the TSP2-1 subtype, which the rest of the phages harbor, has recently been shown to contribute to off-target Citrobacter recognition by Gil et al, explaining our Citrobacter host range results in Table 9 [ 110 ]. In addition, TSP2-1 is known to bind and degrade the O:157O-antigen on Shiga toxin (Stx) producing E. coli , which hinted at their ability to infect the O157:H7 clinical strains [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…Typhimurium, S. Derby, S . 4.12:i:-, S. 4.5.12:1:, S. enteritidis, and S. Goettingen O:4 and O9, explaining why Salmonella is a common host [ 48 , 110 ]. Analysis of the final tail fiber, TSP4, revealed FrontPhageNews contains a unique TSP4 among these six phages, which could explain its inability to infect S. Heidelberg; however, TSP4-2 has been suggested to recognize E. coli O:78 [ 49 ].…”
Section: Resultsmentioning
confidence: 99%